2020
DOI: 10.2507/ijva.6.2.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Motives of Young Audience for Theatre Attendance

Abstract: This paper presents scientific research at the national level in the Republic of Croatia, i.e. the analysis of the motives for the arrival of the younger age group, the generation Y so-called millennials and generation Z's in city and national theatres. The institutions of culture in the Republic of Croatia are always trying to find the best way to contain existing and attract new audiences. The aim of this paper is to investigate the development of young theatre audiences, i.e. their motives, but also the obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The results of empirical research, which was conducted in cultural institutions (galleries, theaters and museums) in the Republic of Croatia, found that cultural institutions understand the importance and role of unconventional marketing for successful fundraising, which is manifested through an increase in the number of visitors (which affects an increase in their own income) and finally the financial result of the institution. According to the above, unconventional marketing methods have a positive effect on the development of audiences in cultural institutions, especially young audiences (Buljubašić, 2020;, and cultural institutions should use such methods if this type of audience is their target group. Likewise, the increased number of visitors or audiences is extremely important for potential sponsors because the audience is extremely important for the provider of sponsorship funds, given that the goal of providing such funds is usually promotion, recognition and image (Mihaljević, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of empirical research, which was conducted in cultural institutions (galleries, theaters and museums) in the Republic of Croatia, found that cultural institutions understand the importance and role of unconventional marketing for successful fundraising, which is manifested through an increase in the number of visitors (which affects an increase in their own income) and finally the financial result of the institution. According to the above, unconventional marketing methods have a positive effect on the development of audiences in cultural institutions, especially young audiences (Buljubašić, 2020;, and cultural institutions should use such methods if this type of audience is their target group. Likewise, the increased number of visitors or audiences is extremely important for potential sponsors because the audience is extremely important for the provider of sponsorship funds, given that the goal of providing such funds is usually promotion, recognition and image (Mihaljević, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…have a more significant impact than conventional forms of promotion (guest appearances on national and local television and radio stations, advertising in local daily newspapers and internet portals, etc.). The objective of Buljubašić's (2020) study, which covered 612 respondents, was to determine the role that advertising activities play in theater attendance among young audiences. The conclusion was that generation Z prefers advertising on social networks and will be attracted to cultural and theater events in this way, while generation Y, for example, will be attracted to the same events by the recommendation of a friend.…”
Section: Previous Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…The diversification of funding sources, according to Čopič (2011), is the basis for a healthy future and strengthens the financial resilience of cultural organizations. For other authors, it is one of the prerequisites for gaining stability and establishing conditions for the survival of organizations in turbulent times, but also one of the key parameters for evaluating the success of its development (Dragojević and Dragičević-Šešić, 2008), as well as the organization's readiness for changes in the environment, creating greater credibility and recognition of the organization in the public while increasing the quality of the program itself (Miletić, 2014: 7), which ultimately contributes to the development of the audience (Buljubašić, 2020) and a better financial result of the organization (Bestvina Bukvić, Borić Cvenić and Buljubašić, 2017).…”
Section: Introductionmentioning
confidence: 99%